Penerapan Metode Transportasi dan Transhipment Menggunakan Linear Programming dalam Efisiensi Biaya Distribusi Barang - Fikri Husin Batubara; Rina Widyasari (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Goods delivery services or expedition services are now increasingly in demand by people in Indonesia every day. One of the most popular shipping services is the company PT. Tiki Jalur Nugraha Ekakurir (JNE), delivery of goods cannot be separated from the important role of the distribution channel, so that problems that arise in the distribution of goods at PT. JNE are the very expensive cost of shipping goods, which causes the company to incur large costs and suffer losses if the problem occurs. This distribution is not complete. The transportation model is used to solve distribution problems experienced by PT. JNE by applying the north west corner, least cost, vogel's approximation and russell's approximation methods as a comparison solution for problem solving. Then the efficient method will be proven by the linear programming method with the help of LINDO software and a sensitivity test to prove the correctness of the transportation model. With the completion of this model, the aim is to streamline the cost of distribution of goods at PT. JNE, from the results of the research on the distribution of goods that is most efficient with the transportation model, namely the vogel's approximation method with a total cost of Rp. 1.018.500.